The Difference Of Comfort And Anxiety Level In Third Trimester Pregnant Women With Osoc And Conventional Assistance - Arum Meiranny; Muliatul Jannah (Alma Ata University Press, 2019)
Anxiety in pregnant women when facing labor is different. Midwives have to be able to increase the comfort to reduce anxiety. One of the ways is with OSOC assistance, this is an assistance during pregnancy, childbirth, postpartum, newborns until family planning in order to increase maternal and infant health. The aims of this study are to determine the differences in comfort and anxiety of third trimester pregnant women who were given OSOC assistance and conventional pregnancy care at Kendal District Health Center (Puskesmas Kendal) .This research is a quasi experimental study with non equivalent control group design. Samples in this study were 124 third trimester pregnant women at Kendal District Health Center (Puskesmas Kendal). The research subjects were divided into intervention and control groups. In the intervention group, pregnant women were give intervention by OSOC assistance, and the control groups were given conventional pregnancy care. This research was held on July-September 2018. The analysis design used Chi Square. The results showed that there were significant differences (p <0.05), and the influence of OSOC assistance on comforting pregnant women was 2.357, and there were significant differences between anxiety in the third trimester pregnant women with OSOC assistance and conventional pregnancy care, and the influence of OSOC assistance on anxiety pregnant women was 7,703. The conclusion of this study is that there are significant differences between the comfort and anxiety of the third trimester pregnant women with OSOC assistance and conventional pregnancy care.